Strategi Guru dalam Meningkatkan Semangat Belajar Anak di RA Mawaddah Warahmah Medan - Marsya Adriana; Juli Maini Sitepu (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
The Professional Work Experience (PKP) program at RA Mawaddah Warahmah Medan was conducted to enhance students’ understanding of teachers’ strategies in fostering young children’s learning motivation. The objectives were to identify baseline learning motivation, design teacher strategies based on children’s needs, and evaluate their impact on classroom engagement. The methods applied included classroom observation, interviews with mentor teachers, documentation, and participatory assistance through a classroom action approach. The strategies implemented consisted of affirmative communication, the use of concrete media, play-based learning, positive reinforcement, and effective transition management. Findings revealed a significant increase in children’s attention, active participation, and positive expression. Average motivation scores improved by 38% from pre- to post-intervention. Children became more focused, enthusiastic, and actively involved in core learning activities. Teachers also benefited from more conducive classroom environments and new creative teaching ideas. These results emphasize the crucial role of teachers as key drivers of learning motivation and demonstrate that simple yet targeted strategies can generate meaningful impacts. The PKP program is expected to contribute to the advancement of educational knowledge, particularly in implementing innovative, contextual, and child-centered learning approaches in early childhood education.